Local and global aspects of coal in the ASEAN countries - Sagbakken, Haakon Fossum (Elgar Handbooks in Energy, the Environment and Climate Change, 2021)
As the world strives to discontinue the use of coal, Southeast Asia stands out as one of the regions where both mining and consumption of coal are expanding. This is driven by the growing demand for electricity in the member states of the Association of Southeast Asian Nations (ASEAN) and is happening despite both international policy pressure to phase out coal from the global energy system and local resistance to coal mines and power plants. This chapter explores the connections and disconnections between the coal sector in the ASEAN countries and global climate policy. Faced with coal's multifaceted threats to public health, economic prosperity and environmental sustainability, organised opposition to coal has been growing across Southeast Asia since 2010. Opposition is shaped by the availability of political space for activists to protest and constrained by geographical distance and legal restrictions. Resistance to coal in the ASEAN member states has focused mainly on local concerns, but there is a growing emphasis on climate change and sustainable resource management in regional environmental networks.